Design and Development of an IoT-Based Monitoring System for Ammonia Gas, Temperature, and Humidity in Poultry Houses with Automatic Control via Blynk - Hutasoit, Anggiat; Laksmiati, Dewi; Mufid, Zainul (Sean Institute, 2025)
Clean air is crucial in poultry farming as it significantly affects the health and productivity of chickens, as well as the surrounding environment. One of the serious issues often encountered is the odor originating from waste or leftover feed, which produces ammonia gas (NH₃). If not properly managed, this gas can cause stress or even death in chickens and pollute the environment. In response to this problem, this study aims to design an Internet of Things (IoT)-based monitoring system for ammonia gas, temperature, and humidity in chicken coops, featuring automatic control through Blynk in real-time. The system uses an MQ135 sensor to detect ammonia gas and a DHT22 sensor to measure temperature and humidity. Sensor data is periodically transmitted through Blynk for remote monitoring. If ammonia levels exceed the safe threshold (>20 ppm), the system automatically activates an indicator LED, an exhaust fan for air circulation, a pump to spray an ammonia-neutralizing liquid, and a servo to dispose of chicken waste. This system also allows users to manually activate the devices via virtual buttons on Blynk and sends real-time notifications on Blynk when ammonia levels rise or when devices are activated. The test results show that the system effectively monitors coop air conditions and performs actions based on needs. It is expected that this system will enable farmers to more optimally control air quality in chicken coops, thereby improving the health of both chickens and farmers, and achieving better farming efficiency.